Peningkatan Kemampuan Berfikir Kritis Siswa Melalui Pembelajaran Eksperimen pada Materi Larutan Elektrolit dan Non Elektrolit - St Fatimah Azzahra (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
This research is aims to know about the improvement of chemistry learning outcomes of grade X on electrolyte and non electrolyte solutions academic year 2018/2019 through learning experimental method. This research is a class action research couduct in three cycles. The subject of this research is all students of grade X Darussalam Tangerang Selatan of 26 students. Data collection techniques in this research are test score of critical thinking skills. The results of the research that the application of learning experimental method can improve students’ critical thinking skills on topics electrolyte and non electrolyte. Based on the results of the first cycle, the second and the third cycle always increase. The average critical thinking ability in fisrt cycle on is 34,61%. In the second cycle the increase in students’ critical thinking skills increased to 73,07% and completeness in the third cycle. The results of this class action research are the learning experimental method can improve students’ critical thinking skills of students in grade X Darussalam Tangerang Selatan on the electrolyle and non electrolyte solutions. Keywords: critical thinking skills, experimental method